Developing Antiangiogenic Peptide Drugs for Angiogenesis-Related Diseases - K.N. Sulochana; R. Ge (Current Pharmaceutical Design, 2007)
Angiogenesis is regulated by stimulators and inhibitors and involve multiple biological processes including endothelial cell proliferation, migration, cell-cell and cell-matrix adhesion, assembly into tube structures as well as apoptosis. Designing and developing peptides for therapeutic application to inhibit angiogenesis is an important area in antiangiogenic drug development. Small peptides have advantages over proteins for therapeutic application, due to their stability, solubility, increased bio-availability and lack of immune response in the host cell. Endogenous protein angiogenesis stimulators and inhibitors hold vital information for designing antiangiogenic peptides for drug development. These proteins function through their interaction with extracellualr matrix molecules, cell surface receptors, proteases, as well as growth factors and cytokines. Conserved domains such as thrombospondin type 1 repeats (TSRs), kringle domains as well as critical amino acid residues present in these domains are involved in their functions. By exploiting these properties, several small peptides have been designed, synthetically made and being tested for therapeutic efficacy. Peptides derived from type 1 repeat of thrombospondin, alpha 4 and beta 1 chains of laminin, arginine rich N terminus of endostatin, leucine rich repeat 5 of decorin, pigment epithelium derived factor and N terminal of parathyroid hormone are examples of small antiangiogenic peptides derived from endogenous proteins. Such bioactive peptides are further modified physico-chemically to increase their potency and stability. In addition, phage-display library screening and combinatorial approach are also in use to identify novel antiangiogenic peptides targeting tumour and various proteins. This review will provide a comprehensive summary of the current status of the antiangiogenic peptides and their relevance for drug designing and development. Several critical issues that need to be resolved in translating this concept into clinical practice are also discussed.
Keywords: Antiangiogenesis